FORMULATION AND EVALUATION OF PRESS COATED TABLETS OF LANSOPRAZOLE - D., Prasanthi; S., PRASHANTI; G., MEGHANA (International Journal of Applied Pharmaceutics, 2019)
Objective: Lansoprazole an proton pump inhibitor, degrades in acidic environment, hence protection of drug is done by coating the drug with enteric coating polymers. The aim and objective of the present study was to prepare enteric coated delayed release tablets of lansoprazole by using press coating technique. Methods: Core tablets were prepared by direct compression and evaluated for their physico-chemical properties. Press coated tablets were formulated by using different combinations of ethyl cellulose, HPMC E15 and HPMC K4M as a coating layer. Core and coated tablets were optimized by dissolution studies. Fourier transform infra-red spectroscopy (FTIR) and differential scanning calorimetry (DSC) studies were performed to know the compatibility of drug with various excipients. Surface morphology and uniformity of coat was evaluated by Scanning electron microscopy (SEM). Stability of optimized formulation was evaluated according to ICH guidelines. Results: Among the various formulations F5 containing ethyl cellulose: HPMC E15 (10:90) and F9 containing ethyl cellulose: HPMC K4M (25:75) were optimized based on the better drug release within 8 h. DSC studies and FTIR studies revealed compatibility of drug with excipients. Obtained SEM photographs of tablets showed that the surface of core tablet is uniformly coated with coat by press coating. Stability studies showed that the formulations were stable. Conclusion: As a result, delayed release press coated tablets developed in this study delivered lansoprazole in the intestine and protected the drug from degradation.